Review On The Shear Strength Of Clay Subdistrict Of Sukodono Sragen District With The Additional Stabilization Material The Powder Of Wood Charcoal - Al Fatah, Beny; , Ir. Renaningsih, MT (2017)
(A Case Study on Sukodono Clay,Sragen) Soil Sukodono is clay with LL 85.73%, PL 24.69% and PI 61.04% (Pasetyo 2016) .The main problem on soil is the soil condition is less stable (expansive soil). Wood charcoal is used for stabilization materials . The objectives of the research were to find out the physical properties and the value of DST of the original soil from Sukodono Subdistrict of Sragen Regency and the stabilized soil mixture using wood charcoal powder 10%, 15% and 20%. The physical test of soil mixture of waer content and plastic limit rose while the liquid limit, Shrinkage limit, plastic index and pass no.200 down. Based on the original AASHTO ground classification system including group A-7-6 and mixed soil group A-7-5. Based on USCS original and mixed soils including CH group. Standard Proctor test results with the addition of mixed percentage cause the value of optimum water content increase and the weight value of the maximum volume decreased. The result of DST shows the increase of friction angle value in and the decrease of cohesion value which happened due to the addition of material percentage of stabilization. The highest friction angle increase in the mixture of 20% equal to 37,770 and the smallest on a 10% mixture of 33,400. Normal stress values and shear on mixed soil undergo an increase of the original soil value. The largest normal voltage at a 20% percentage is 4.62 kg/cm2 and the smallest value is 3.45 kg/cm2 in the original soil. The smallest shear stress is 1.21 kg/cm2 on the original soil and the largest value at Percentage of 20% of 1.62 kg/cm2.